A patient of zygomaticomandibular syngnathia – Management and review of literature. Issue 6 (November 2018) - Roy Chowdhury, Sanjay Kumar; Saxena, Vivek; Krishnaprabhu, Rajkumar; Shadamarshan R, Arunkumar
Abstract: Syngnathia or the congenital fusion of the jaws is one of the rarest deformities affecting the maxillofacial region. Syngnathia can be classified as 'true syngnathia' and 'pseudosyngnathia' based on the bones involved. 'true syngnathia' is characterised by the fusion of maxilla and mandible while 'pseudosyngnathia is characterised by the fusion of mandible to the Zygoma. A rare case of zygomaticomandibular syngnathia in an 18-month-old girl associated with hemifacial hypoplasia, absent external ear and acoustic meatus on the left side has been reported in this article. The child was taken up for two stage surgery, the first of which was aimed at lengthening of the existing ramus by distraction osteogenesis. The second stage surgery included removal of the distractor, release of the syngnathia followed by interposition using PTFE membrane. Vigorous and meticulous post-operative mouth opening exercises for a period of 06 months have stabilised the mouth opening at 25 mm at the end of a follow up of 01 year. Distraction osteogenesis before the release of fusion proved to be a very effective treatment option for such patients to maintain the height of the ramus post release of fusion. Regardless of the management instituted for the release of fusion, post-operative physiotherapy and parental compliance plays a vital role in the success of the management of these patients.